Pemberdayaan Masyarakat Desa Blimbing dalam Pembuatan Jasimun (Jamu Sistem Imun) sebagai Upaya Peningkatan Imunitas di Masa Pandemi - Prodyanatasari, Arshy (Jurnal Pengabdian Masyarakat (Jupemas), 2023)
The body's immune system is a collection of mechanisms that are owned by living things, where the immune system functions to protect the body from infection by identifying and killing pathogenic substances that attack the body in thousands of different ways. The immune system can be known when there is a failure to produce immunity. During a pandemic, very important to maintain the body's immune system properly, so that it can minimize being infected with the Covid-19 virus. One of the efforts to maintain the body's immune system is to consume healthy food and drink. One of the healthy drinks that can be consumed to maintain the body's immune system is Jasimun (Jamu Sistem Imun). Jasimun is a herbal and healthy drink made with selected ingredients of good quality and rich benefits, including ginger, turmeric, cloves, lemon grass, lime, and palm sugar. The purpose of PkM activity is to invite the public to maintain body immunity by consuming the Jasimun herbal drink. The method used in this activity was demonstration how to make Jasimun to the participants in attendance, where it is very easy and simple to make, simply by boiling all the ingredients medium heat until boiling. Based on the activities carried out, the activity participants were very enthusiastic in participating in the activities and liked the taste of Jasimun was made. This Jasimun product can also be an entrepreneurial opportunity for the community because Jasimun herbal drink products can be commercialized and able to improve the community's economy.